A comparative study of teacher preparation in the Kingdom of Saudi Arabia, the United States of America, Japan, Singapore and Finland - Abuzaherah, Nadia Obidullah; AlHarthi, Reham Khaled; Alhomoud, Safiah Ali; Al-Talhi, Asmaa Faiez (Journal of Educational and Psychological Sciences, 2022)
The current study aimed at a comparison between the Kingdom of Saudi Arabia, the United States of America, Japan, Singapore and Finland, in their teacher preparation programs and to show the similarities and differences between them. Considering the experiences of comparison countries?The study confirmed that the Kingdom of Saudi Arabia, after Vision 2030, has developed rapidly in its aspects of teacher preparation, and concluded with several recommendations, the most important of which are: Working on the actual development of the objectives, content and plans of teacher preparation programs in the Kingdom of Saudi Arabia, with reference to the necessity of integration and coordination between the three aspects of the teacher preparation program (academic, cultural, professional), and the development of effective training programs aimed at developing the teacher’s performance with a focus on e-learning, the necessity of paying attention to the practical and applied aspect of teacher preparation programs and increasing interest in them and balancing between them and the theoretical side, reviewing the admission policy in educational colleges According to the policies of the comparison countries, and benefit from them.
Keywords: teacher preparation; teacher preparation programs; country experiences; the United States of America; Singapore; Malaysia; Finland